Experimental study of pedestal turbulence on EAST tokamak. (14th July 2015) - Gao, X.; Zhang, T.; Han, X.; Zhang, S.B.; Kong, D.F.; Qu, H.; Wang, Y.M.; Wen, F.; Liu, Z.X.; Huang, C.B.
Abstract: Turbulence in the pedestal region of the EAST tokamak has been observed and studied using reflectometry. In lower hybrid wave (LHW) or neutral beam injection (NBI) dominated heating plasma, a coherent mode (CM) was usually observed in the ELM-free phase just after the L-H transition. The CM rotated in the electron diamagnetic drift (EDD) direction in the laboratory frame with a poloidal wave number ( k θ ) of 0.5 cm −1 –0.7 cm −1 and its frequency usually chirped from 80 – 100 kHz down to 40 – 50 kHz as the pedestal evolved. The appearance of this mode reduced the increasing rate of pedestal pressure, implying that the CM may have an effect on outward pedestal transport. This mode can exist every ten milliseconds and is finally replaced by broadband (BB) fluctuation in the later ELM-free phase. It was found that the appearance and disappearance of the CM was correlated to the pedestal pressure. In the inter-ELM phase, the pedestal turbulence is generally dominated by BB fluctuation with poloidal wave numbers from 0 to 3 cm −1 rotating in the EDD direction in the laboratory frame. Analysis shows that the pedestal pressure increasing rate d p e, ped /d t decreases with the amplitude of the BB fluctuation, implying that the BB fluctuation may play an important role in pedestal evolution. The preliminary observation on the fluctuation just inside the pedestal top is also presented.